The Missing New Funds - Zhu, Qifei (Management Science, 2020)
Many papers in the mutual fund literature rely on a sample that matches the Center for Research in Security Prices (CRSP) mutual fund database with the fund holdings data from Thomson Reuters (TR) s12 database. I document that about 58% of newly founded U.S. equity mutual fund share classes in the CRSP mutual fund database from 2008 to 2015 cannot be matched to the TR database. Funds that are missing from the TR database tend to be smaller, have higher turnover ratios, receive higher fund flows, and have higher four-factor alphas. These differences are robust within same cohorts of funds. Index funds and exchange-traded funds are more likely to be omitted than actively managed funds. This paper was accepted by Tyler Shumway, finance.